Toward a Constructivist Model of Radicalization and Deradicalization: A Conceptual and Methodological Proposal - Winter, David A.; Feixas, Guillem (Frontiers in Psychology, 2019)
This article identifies common features of existing models of radicalization and deradicalization, such as the transition from uncertainty to certainty, before integrating these in a model based upon personal construct theory. It is proposed that the personal construct concepts of validation and invalidation are particularly relevant to processes of identity change such as radicalization and deradicalization. Thus, it is argued that radicalization occurs when major invalidation of an individual’s construing is followed by the development of a new radicalized view of the world that provides a turning point in his or her sense of identity and a more structured and certain view of the world. There is likely to be seeking out of validation for this view in interactions with others who share similar views or by extorting evidence for the individual’s radical constructions. These constructions are likely to involve extreme negative views of another group, by contrast to members of which, and possibly by taking extreme action against this group, the individual’s new self-construction may become further defined. These same processes can be seen to operate in deradicalization, and it will, therefore, be argued that the model has implications for the development of deradicalization programmes. A further advantage of the model is that it has an associated personal construct methodology, particularly repertory grid technique, that may be used to investigate processes of radicalization and deradicalization. As illustrations of such investigations, results will be summarised from a repertory grid study of Salafist Muslims in Tunisia, some of whom had returned from fighting in Syria; and an analysis of the writings of the Norwegian mass murderer Anders Breivik. The findings of these investigations are argued to be consistent with the personal construct model of radicalization and deradicalization.